Listening to the Voices of Students Who Studied Abroad : Students and Their Agency to Maximize Their Abroad Experiences - Raby, Rosalind Latiner; Ward, Rupert; Rhodes, Gary (Journal of International Students, 2021)
This article learns from student voices about how their education abroad experiences were shaped by their agency. Interviews and focus groups were conducted with 22 U.S. community college and university students and with U.S. faculty and U.K. senior staff who worked at a Study Abroad Center in London. The study focuses on what the students said were the impact they had from studying abroad, what they said about institutional support that they needed prior to studying abroad, and what they said about their changing sense of being while studying abroad. Counterbarrier construct and agency theories were used to ground the findings. The findings showed that these students used their agency to influence their decisions to study abroad, to find the strength to transcend weak institutional support services, and to recognize their own personal, social, and critical skills development as a result of studying abroad.